Space observations of AA Doradus provide consistent mass determinations. New HW-Vir systems observed with TESS. Issue 2 (4th March 2021) - Baran, A S; Østensen, R H; Heber, U; Irrgang, A; Sanjayan, S; Telting, J H; Reed, M D; Ostrowski, J
ABSTRACT: We present an overview of eclipsing systems of the HW-Virginis (HW-Vir) type, based on space observations from the Transiting Exoplanet Survey Satellite ( TESS ) mission. We perform a detailed analysis of the properties of AA Doradus (AA Dor), which was monitored for almost a full year. This excellent time series data set permitted us to search for both stellar pulsations and eclipse timing variations. In addition, we used the high-precision trigonometric parallax from Gaia Early Data Release 3 to make an independent determination of the fundamental stellar parameters. No convincing pulsations were detected down to a limit of 76 parts per million; however, we detected one peak with false alarm probability of 0.2 per cent. 20 s cadences being collected during Year 3 should confirm or reject our detection. From eclipse timing measurements we were able to confirm that the orbital period is stable, with an upper limit to any period change of 5.75 × 10 −13  s s −1 . The apparent offset of the secondary eclipse is consistent with the predicted Rømer delay when the primary mass is that of a canonical extended horizontal branch star. Using parallax and a spectral energy distribution corroborates that the mass of the primary in AA Dor is canonical, and its radius and luminosity are consistent with an evolutionary state beyond core helium burning. The mass of the secondary is found to be at the limit of hydrogen burning.